(untitled) (Research, Society and Development, 2021)
The rapid evolution of technology through globalization and opening of markets allows companies to be increasingly flexible in their operational and also organizational processes, searching for a perfect production and marketing system as well as new customers for their performance, enabling inclusion in innovative processes making it competitive and profitable. The main objective of the article is to identify the main elements in the implementation of methodologies applied in industry 4.0. The case study methodology was used for its degree of relevance with theme, and for the scope that can be used in such a way that it can be a guide for other micro and small companies that are in the process of giving or even applying these methodologies. The results were positive for the interviewees, which reinforces the importance of the theme.